Real-Time Face Age Detection System Based on Deep Neural Networks with MediaPipe Optimization for Enhanced Accuracy - muhaimin iskandar; Nur Azizah; Firman Jaya (Jurnal Sistem Cerdas, 2025)
The transformation of machine learning and computer vision technology enables computers to automatically learn complex visual patterns, forming the foundation for biometric applications such as identity authentication, face detection, and demographic analytics. Face age estimation predicts age based on facial characteristics in digital images with high accuracy. Handcrafted feature-based approaches such as Histogram of Oriented Gradients (HOG) and Local Binary Patterns (LBP) are less stable against variations in lighting, camera orientation, and facial expressions. Deep learning, particularly Deep Neural Networks (DNN), improves accuracy through automatic hierarchical feature extraction. However, raw image-based methods have high computational loads and require large GPUs, which are less than ideal for real-time use on limited devices. This research proposes a DNN-based age estimation system optimized through MediaPipe Face Mesh geometric features. The system consists of five layers: input, feature extraction (468 facial landmarks), optimization with Principal Component Analysis (PCA) for 64 features, DNN regression (three hidden layers), and output. A custom dataset of 1,235 facial images (ages 3–40 years) was divided into 80% training and 20% testing. The model was trained with the Adam optimizer (learning rate 0.001, epochs 500, loss MAE). Evaluation results: MAE 0.56 years, RMSE 1.94 years, R² 0.9726. Tolerance accuracy: 91% (±1 year), 96.7% (±2 years), 97.5% (±3 years), 99.2% (±5 years). An efficient system for real-time use on low-computing devices, supporting biometric applications such as security, content filtering, personalization, and health. This research contributes to accurate, lightweight, and adaptive age estimation systems.